The use of faecal Na concentration as an indicator of Na deficiency in lactating crossbred cows - Khalili, M.; Varvikko, T.; Lindgren, E. (Swedish University of Agricultural Sciences, 1991)
An experiment was carried out with four rumen fistulated crossbred Friesian X Zebu lactating cows to evaluate the Na content of faeces as an indicator of Na deficiency in cattle. In addition, the effect of NaCl supplementation on the animal performance and rumen parameters was examined. The cows were fed a basal diet of oat-vetch hay and concentrate containing low Na. The diets were supplemented as follows; Diet 1, no supplement (low barley, low Na); Diet 2, 3 g NaCl kg total dietary DM (low barley, adequate Na); Diet 3, 3.0 kg barley (high barley, low Na) and Diet 4, 3.0 kg barley and 3.o g NaCl kg total dietary DM (high barley, adequate Na). Intake significantly increased after NaCl supplementation when high barley was fed. Provision of NaCl significantly increased milk production. High consumption of barley also increased milk production irrespective of NaCl. Increased barley consumption decreased rumen fluid PH. The concentration of Na in the rumen fluid supernatant decreased on low Na diets, but the concentration of K increased. The concentration of Na in blood plasma did not change following the NaCl supplementation. Faecal Na and Na/K ratios were lower on the Na deficient than on the NaCl supplemented diets. There was no variation in Na and Na/K ratios in faecal samples collected at 0,3,6, and 8 h after the morning feed on two consecutive days. Faecal Na on the Na deficient diets were below the critical level of 1 g kg DM. It would appear that the determination of Na in grab samples of faeces is a practical procedure for determining the Na status of cattle.